2017
DOI: 10.1038/mp.2017.208
|View full text |Cite
|
Sign up to set email alerts
|

Association of genetic ancestry with striatal dopamine D2/D3 receptor availability

Abstract: Despite ethnic differences in allele frequencies of variants in dopaminergic genes associated with dopamine D2/D3 receptor availability (D2R), no study to date has investigated the relationship between genetic ancestry and striatal D2R. Here, we show that ancestry informative markers significantly predict dorsal striatal D2R in 117 healthy ethnically diverse residents of the New York metropolitan area using Positron Emission Tomography (PET) with [11C]raclopride (p<0.0001), while correcting for age, sex, BMI, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 57 publications
0
20
0
Order By: Relevance
“…Our primary analysis fitted a linear regression model with striatal dopamine synthesis capacity as the dependent variable, and anterior cingulate cortex glutamate concentrations as predictor. Given the possible effects of age, 21 sex, 22 , 23 and ethnicity 24 on imaging measures, we did secondary exploratory analyses that adjusted for these demographic factors. Additionally, as antipsychotic treatment could influence imaging measures and symptom severity ratings 25 , 26 we added medication status at time of scan (on antipsychotic treatment or drug free) to this model.…”
Section: Methodsmentioning
confidence: 99%
“…Our primary analysis fitted a linear regression model with striatal dopamine synthesis capacity as the dependent variable, and anterior cingulate cortex glutamate concentrations as predictor. Given the possible effects of age, 21 sex, 22 , 23 and ethnicity 24 on imaging measures, we did secondary exploratory analyses that adjusted for these demographic factors. Additionally, as antipsychotic treatment could influence imaging measures and symptom severity ratings 25 , 26 we added medication status at time of scan (on antipsychotic treatment or drug free) to this model.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, there is preliminary evidence of lower CB 1 availability in healthy subjects of Indian ancestry compared to those of European and African ancestry [39]. A recent analysis of raclopride studies demonstrated significant differences in binding based on ancestry [106]; thus, ancestry may deserve greater consideration in human PET studies than previously assumed. Other confounding factors could include length of illness and symptom severity, which were correlated with CB 1 availability in some studies (Supplemental Tables 1 and 2).…”
Section: Discussionmentioning
confidence: 95%
“…Surprisingly, we saw the effect of decreasing DAT with increasing age in opioid and not alcohol users, but since this effect is seen in healthy humans as well [57], it might not be opioid specific. Especially when interpreting the result of lower D2 receptor availability in alcohol and in opioid users, other moderating factors than those we could investigate in our analyses must be kept in mind, since former research on D2 receptor availably in non-users revealed further possible influencing factors as, for example, the influence of social dominance [58], genetic ancestry [59] or sleep deprivation [60].…”
Section: Discussionmentioning
confidence: 99%